Landscape Patterns and Ecosystem Services Are Critical for Contributions to Sustainable Development Goals - Xue Miao; Zihao Guo; Congbin Leng; Jinliang Hou; Qingping Cheng; Hede Gong (Ecosystem Health and Sustainability)
The ecosystem services (ESs) and landscape patterns (LPs) in a region have a marked impact on human production and life and even play an important role in the achievement of regional Sustainable Development Goals (SDGs). Given the limited consideration of LPs and ESs on SDGs in current research, it is especially crucial to provide comprehensive and targeted policy support for regional sustainable development in less developed areas from an environmental perspective. Utilizing the Lincang National Sustainable Development Innovation Demonstration Zone as a case study, we developed an evaluation index system for the SDGs at the county level in Lincang City. This system was established based on extensive field surveys, visits, and data collection conducted with local government departments and relevant organizations between 2021 and 2022. Our study found that there was significant spatial heterogeneity in the relationship between SDGs and LPs or ESs in each county. Therefore, the regulation of ESs and the optimization of LPs should not adopt a one-size-fits-all approach; rather, targeted measures should be implemented for specific SDGs. Additionally, there is a significant dual-factor interaction enhancement between ESs and LPs in explaining each SDG. This implies that promoting the synergy between ESs and LPs can effectively drive the achievement of certain SDGs. Overall, this study provides critical scientific decision-making references for local governments in promoting the realization of SDGs and the construction of a more beautiful Lincang. In addition, this study provides Chinese experience and the Lincang plan for neighboring countries such as Myanmar and Laos.